Analisis Hubungan Kebutuhan Pangan, Pertumbuhan Populasi, dan Pembangunan Ekonomi di Provinsi Indonesia Tahun 2023: Pendekatan Regresi Non-Linier Berbasis Gamma - Noh, Fananda Putri M. (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study investigates the complex relationship between food demand, population growth, and economic development across Indonesian provinces in 2023. Using a non-linear regression approach based on the Gamma distribution, this research aims to uncover non-linear patterns and interdependencies among these variables. The analysis includes key factors such as Human Development Index (HDI), population growth rate, Gross Regional Domestic Product (GRDP), and unemployment rates in February and August. The findings reveal that HDI significantly influences food protein demand, while GRDP, population growth, and unemployment rates exhibit non-significant impacts. The Gamma distribution is shown to effectively model the asymmetric and highly variable data characteristics. This approach provides insights into regional disparities and guides evidence-based policymaking to enhance food security and economic equity in Indonesia. The study underscores the necessity of integrating human development strategies in addressing food demand challenges.